Interactive media of respiratory system material “resysmart” based on problem-based learning - Luthfi Rahayu Ningsih; Mieke Miarsyah; R. Rusdi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
The meaningful learning of respiratory system will be enacted by students through the utilization of problem-based learning interactive media. This study aimed to develop problem-based interactive learning media on respiratory system material. This Research and Development (R&D) was conducted based on Borg and Gall with ten stages, namely: 1)  research and information collecting, 2) planning, 3) developing, 4) preliminary field testing, 5) main product revision, 6) main field testing, 7) operational product revision, 8) operational field testing, 9) final product revision, 10) dissemination. The results of the research showed that the materials score achieved by the media developed was 90% (very good), while the media presentation score was 83% (very good); in addition, the language score gained was 99% (very good). Thus, the average score was 91% (very good) which means that the interactive learning media developed was recognized as very good to be implemented in respiratory system learning for eleventh graders. To go further, the teachers and students gave their response to the media as high as 80% (very good) and 89% (very good) respectively. To conclude, “resysmart” interactive media is strongly recommended to be used in respiratory system learning for eleventh graders.